A Robotic Arm Prototype for Automated Packaging of Chocolates with Artificial Intelligence - Cerecerez Jimenez, Gustavo; Quito Carrión, Angélica; Córdova, Luis; Abedrabbo, Faruk; Mosquera, Guillermo; Venegas, Marcela (LACCEI, 2025)
This paper details the development of an advanced robotic arm designed to package chocolates efficiently in a small-scale process. The arm features a Prismatic-Revolute-Revolute) configuration and is equipped with a Universal Vacuum Grip to handle chocolates precisely. Its construction utilizes PLA 3D printed parts for the mechanical structure and flexible TPU belts to ensure optimal movement control. Electronically, the system is powered by NEMA 17 motors, controlled by an Arduino board and a CNC interface for precision motor management. The programming, conducted in Python, integrates artificial intelligence through computer vision techniques to enhance the accuracy and adaptability of the packaging process. A graphical user interface was developed, allowing intuitive control and sequence management of the robotic arm's operations. The incorporation of artificial intelligence enabled the robotic arm to identify successfully and sort chocolates of varying types, greatly enhancing packaging efficiency. The results demonstrate the arm's capability to consistently place chocolates in trays, thereby augmenting productivity, reducing human error, and maintaining packaging quality. This project underscores the significance and potential of integrating automation and artificial intelligence in the food packaging industry.